Pemberian Grit pada Ayam Buras Memperpanjang Saluran Pencernaan, Menambah Bobot Ampela, dan Bobot Tulang Karkas (PROVISION OF GRIT TO NATIVE CHICKEN IMROVED THE DEVELOMPMENT OF GASTRO INTESTINAL TRACT AND INCREASE CARCAS BONE) - Sabuna, Cytske; Bale-Therik, Jublin Franzina; Mulyantini, Ni Gusti Ayu (Jurnal Veteriner; Vol 16 No 1 (2015), 2015)
Commonly, native chicken is raised in an extensive management system. The chickens were free toscavenge in the backyard, and eat a wide variety of feeds including, rice, corn, insects, or even grit. Grit is anabrasive material that can help to grind feedstuffs and use as a source of mineral for chicken. In anintensive farming system, native chickens are given full feeding program throughout the production period,without grit. The objective of this research was to study the development of gastrointestinal tract andcarcass bone of native chickens supplemented to grit. Eighty chickens were used in the study usingrandomized block design. The four treatments were: R0 = basal feeds without grit ; R1 = R0 + grit 0,25% ofbody weight ; R2 = R0 + grit 0,50% of body weight ; R3 = R0 + grit 0,75% of body weight. The results showedthat administration of grit up to the level of 0.75% body weight significantly increased grit consumption,digestive tract length, gizzard weight and carcass bone weight of native chicken.
Keywords: native chickens, grit, gastrointestinal and carcass bone